Clustering of Provinces in Indonesia based on Maternal Health Indicators - Herti Maryani; Lusi Kristiana; Astridya Paramita; Pramita Andarwati; Nailul Izza (Institute of Medico-legal Publications Pvt Ltd, 2021)
Indonesian health issues that deserved top priority was maternal and child health because it determines thequality of the human resources of future generations. The objective of this research is to analyze the clusteringof provinces in Indonesia based on maternal health indicators. This cross-sectional study was conducted in34 provinces using secondary data from the Basic Health Research and Statistics Indonesia. Analysis ofprovincial clustering used FUZZY C-MEANS. Analysis produces six clusters. Cluster 2 has a high meanvalue of maternal health indicators that exceeded the Indonesian target, consisting of the provinces of DKIJakarta, DI Yogyakarta, and East Nusa Tenggara. Cluster 2 was formed by the value equation variable Age offirst mating, Ownership of maternal and child health monitoring book, Vitamin A Provision, K4, postpartumvisits, Iron supplementation tablets consumption and Childbirth delivery in health facilities. Indicators ofownership of the maternal and child health monitoring book for pregnant women had met Indonesia targetin all clusters. Meanwhile, the active participation of family planning program indicator was still below theIndonesia target in all clusters.